grape seed extract role against L-Thyroxine effects on thyroid gland and lipid profile - Ahmed AL-Naely; Dalal Shattnan (Al-Qadisiyah Journal of Pure Science, 2021)
The aim of the current study is identify role grape seed extract on thyroid gland tissues, hormones and lipid profile disorders induced by L-Thyroxine by used dose 20 mg/kg. The experience including 40 male rats randomly divided into five groups each group consist of 8 animals,  grape seed extract dose 150mg/kg  daily for 30-day.Results showed that the animals treated with L-Thyroxine had significant increase(P<0.05) in  thyroid hormones concentration  and dencrease TSH hormone compared with their normal range level in the control group and the rest of the experiment groups, While groups in which grape seed extract (GSE) interferes with drug showed improvement in thyroid hormones level closer to normal range in control group. Also the results showed significant decrease (P<0.05) in TC, TG HDL, vLDL and in L-Thyroxine group, in addition to  thyroid tissue damage.  On the other hand animals treated by both grape seed extract (GSE) and drug showed significant improvement(P<0.05) in TC, TG, HDL, vLDL, LDL and thyroid tissue compared with groups treated with drug only. It was concluded from this study that grape seeds extract had protective role against damage caused by L-Thyroxine.